Development and Implementation of Pediatric Critical Care Focused Simulation Workshop and Program in India - Utpal S Bhalala; Jesal Sadawarte; Sameer Sadawarte; Vishal Baldua; Swati Garekar; Rahul Pandit; Maninder Dhaliwal; Vinay Joshi; Preetha Joshi; Mahesh Mohite; Chandrahas Deshmukh; Rakshay Shetty; et al. (Wolters Kluwer Medknow Publications, 2014)
Simulation-based learning has become a pait of residency and fellowship training 111 many training programs in the United States. But. it has not been incorporated into the pediatric critical care medicine training 111 the developing countries like India. Simulation-based training allows rapid and repetitive learning of skills necessaiy to provide a high quality and safe care to critically ill children. There is a need to explore simulation as a tool to train pediatric and pediatric critical care medicine practitioners in the developing world. This is particularly pertinent to Indian subcontinent in which pediatric critical care medicine has grown by leaps and bounds over last decade. We hereby present one of the earliest reports of development and implementation of pediatric critical care focused simulation workshop and program 111 India.